PENGARUH REPUTASI AUDITOR, AUDIT CLIENT TENURE DAN OPINION SHOPPING TERHADAP OPINI AUDIT GOING CONCERN (STUDI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021) - Rean Ifanto Pratama; Hernadianto, Hernadianto; Ahmad Sumarlan; Ahmad Junaidi (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to determine the effect of auditor reputation, client tenure audit and opinion shopping on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. This research was conducted on the Indonesia Stock Exchange (IDX) by accessing the www.idx.co.id page to obtain information disclosed in the company's annual financial statements. The population in this study was 193 companies, with sampling based on certain criteria using purposive sampling techniques so that the number of samples obtained amounted to 56 companies. The statistical method used is logistic regression analysis. The results obtained from this study show that the auditor's reputation partially affects the going concern audit opinion by 0.038 which means <0.05, the client tenure audit partially has no effect on the going concern audit opinion by 0.290 >0.06, and the opinion shopping partially does not affect the going concern audit opinion by 0.093 >0.05. Keywords: Auditor Reputation, Audit Client Tenure, Opinion Shopping, Audit Opinion Going Concern